Extensive reading among Agroecotechnology students: What and why they read? - Mushoffan Prasetianto; Rizkiana Maharddhika (Intelektual Pustaka Media Utama, 2022)
Reading is a pivotal skill for non-English department students as a vehicle to update their knowledge. One of reading activity which is beneficial is extensive reading. Several studies have proved the advantage of extensive reading, but study regarding what reading material is read by students is under explored. To fill this gap, this research aimed to uncover what non-English department students read during extensive reading program and why they chose that theme. The participants were Agroecotechnology students (n=52). The data was collected from the reading log sheet and participant interview. The reading log sheet was analyzed by the researcher to find the theme of the text that students read. The interview was conducted in Indonesian to make students at ease. After the interview, the transcript was written and translated into English. The result shows that there are 32 types of themes with various frequency distributions. Theme that students read is mainly caused by their hobby, favorite idol, and a senior student who influence them to read certain theme.